2022
DOI: 10.3389/fcvm.2022.850674
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Monitoring and Heart Failure in Advanced Breast Cancer Patients Treated With Trastuzumab in Ontario, Canada

Abstract: BackgroundTrastuzumab has improved patient outcomes in HER2 + breast cancer (BC) but carries a risk of cardiotoxicity. Routine cardiac imaging is recommended for advanced breast cancer (aBC) patients during trastuzumab treatment despite a lack of evidence that this improves patient outcomes. This study was conducted to understand predictive factors for cardiac events and determine the impact of cardiovascular monitoring in aBC.MethodsThis retrospective population-based cohort study included aBC patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The advent of anti-HER2 targeted therapy has marked a pivotal shift in the management of HER2-positive breast cancer, significantly enhancing patient outcomes. Nonetheless, these therapeutic strides come with challenges, particularly as treatments based on trastuzumab have been associated with increased cardiac toxicity risks [8,9,13]. This discussion aims to contextualize our research findings, focusing on adherence to monitoring guidelines, the emergence of cardiotoxicity, and the pressing demand for precise risk assessment tools.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The advent of anti-HER2 targeted therapy has marked a pivotal shift in the management of HER2-positive breast cancer, significantly enhancing patient outcomes. Nonetheless, these therapeutic strides come with challenges, particularly as treatments based on trastuzumab have been associated with increased cardiac toxicity risks [8,9,13]. This discussion aims to contextualize our research findings, focusing on adherence to monitoring guidelines, the emergence of cardiotoxicity, and the pressing demand for precise risk assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab is recommended as an adjunctive therapy in conjunction with chemotherapy for patients with breast cancer who exhibit HER2 overexpression. This combined approach underscores the importance of trastuzumab in the comprehensive management of HER2-positive breast cancer cases [8][9][10]. Indeed, it should be noted that HER2 is expressed not only in cancer cells but also in the myocardium, specifically within the myocytes of the heart.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Several research have failed to identify the risk factors that have a signi cant in uence in the development of heart failure. A limited number of studies found that age and the number of cycles signi cantly increase the risk of heart failure [23,24]. Moreover, the administration of doxorubicin and cyclophosphamide concurrently could raise the risk of cardiotoxicity by up to 27% [25].…”
Section: Discussionmentioning
confidence: 99%